Prediktor Mekanisme Koping Terhadap Stres Pembelajaran Pada Mahasiswa Keperawatan - Kurniastuti, Margaretha; Scholastica Fina Aryu Puspasari (LPPM ITEKES Mahardika, 2026)
Background : Nursing students face academic demands that may negatively affect mental health and academic achievement. Coping mechanisms are essential strategies for managing stressors; however, the effectiveness of different coping types in influencing learning-related stress remains inconsistent.Objective: This study aimed to analyze coping mechanisms as predictors of learning-related stress among students. Methods: This study employed a quantitative cross-sectional design. A total of 71 students were included using a total sampling technique. The instruments used were the Brief COPE questionnaire and the Perceived Stress Scale (PSS-10). Data were analyzed using multiple linear regression with a significance level of 0.05. Results: The results of the analysis showed that the predictors of less useful coping [T1.1][MK1.2] had a significant effect on learning stress (p = 0.003). Conclusion: The use of less useful coping is a predictor of learning stress in nursing diploma students compared to problem-focused coping and emotional-focused coping. Strengthening adaptive coping and reducing the use of maladaptive coping needs to be the focus of educational interventions and student mentoring.